Production Allocation on Commingled Two Layer Well Using Fingerprint Method - Fahrudin Zuhri; Rachmat Sudibjo; R. S. Trijana Kartoatmodjo (Journal of Earth Energy Science, Engineering, and Technology, 2018)
Production proportion ratio study of commingled well two layers reservoir has been developed by geochemistry approaching, with oil reservoir fingerpint methode by using Gas Chromatography then processed by Chemstation software. The study is developed to solve the commingled well production alocation problem in oil field. There are 4 oil samples will be analyzed to represent each layer and commingle production oil sample in 2009 and 2015.Result of study, figures out that oil fingerprint from commingle production has a difference as long as production time. Oil sample that taken from different commingle production time is predicted to produce a different ratio contribution form each layer of reservoir. Every layer reservoir has a different contribution from 2009 to 2015. Result of production proportion ratio study can be applied to decisionmaking of reservoir developement in an oil field, especially for well completion and enhanced oil recovery. This methode is proven to be a solution of commingle production problem of two layers reservoir. Fingerprint methode to determine production proportion ratio of commingled well production is the first in Indonesia.